Teacher Training and Professional Development for Implementing AI-Based Educational Tools (Journal of Asian Development Studies, 2024)
This study explored the impact of teacher training and professional development on the integration of AI-based educational tools in classrooms. A survey of 200 teachers from primary, secondary, and higher education institutions was conducted to assess their familiarity, confidence, and experiences with AI tools. Results revealed that while 40% of teachers were somewhat familiar with AI tools, only 5% expressed high confidence in their ability to use these technologies. Moreover, 70% of teachers had not received any professional development for AI, and a statistically significant correlation (χ² = 16.54, p = 0.002) was found between professional development participation and increased confidence. The most significant barriers to AI integration were a lack of training (60%) and insufficient resources (40%). These findings underscore the necessity for targeted, continuous professional development to improve educators' readiness and ability to effectively utilize AI tools in their teaching practices.